Anion⋯anion (MX3−)2 dimers (M = Zn, Cd, Hg; X = Cl, Br, I) in different environments. Issue 25 (22nd June 2021) - Wysokiński, Rafał; Zierkiewicz, Wiktor; Michalczyk, Mariusz; Scheiner, Steve
Abstract : MX3 − (M = Zn, Cd, Hg; X = Cl, Br, I) ions can engage with one another in one of two different modes, despite their strong mutual coulombic repulsion. Noncovalently bonded stacked dimers of like-charged monomers are stabilized by the spodium bonds. Abstract : The possibility that MX3 − anions can interact with one another is assessed via ab initio calculations in gas phase as well as in aqueous and ethanol solution. A pair of such anions can engage in two different dimer types. In the bridged configuration, two X atoms engage with two M atoms in a rhomboid structure with four equal M–X bond lengths. The two monomers retain their identity in the stacked geometry which contains a pair of noncovalent M⋯X interactions. The relative stabilities of these two structures depend on the nature of the central M atom, the halogen substituent, and the presence of solvent. The interaction and binding energies are fairly small, generally no more than 10 kcal mol −1 . The large electrostatic repulsion is balanced by a strong attractive polarization energy.